الام في الفن العراقي المعاصر من التعبير الشخصي ألى الرمزية الثقافية (دراسة تحليلية ) (Journal of the College of Basic Education, 2025)
Iraqi painting is naturally subject to different European influences and schools, and on the other hand to the cultural heritage in a way that makes the process of research and investigation into the method of presenting and selecting topics a task worthy of study. In our research entitled (The Mother in Contemporary Iraqi Art from Personal Expression to Cultural Symbolism), the researcher seeks to uncover those perceptions and cases through which maternal feelings were embodied in an analytical and descriptive approach in order to achieve the research goal. In the first chapter, the researcher identified the research problem, its importance, and the approach followed, and defined the concept of the mother and her embodiment in a manner consistent with modern Iraqi art to achieve the research goal. Through the second chapter and in the first section, the topic of the mother was addressed through a historical vision to determine her position and impact in society. In the second section, her role in society was studied. In the third section, the researcher studied the nature of contemporary Iraqi painting in order to determine the characteristics of the properties of Iraqi painting due to its effective role in determining the research environment. In the third chapter, the researcher conducted the analysis through samples (of three female artists who have an active role in the Iraqi plastic arts movement according to specific characteristics according to a descriptive analytical approach to form and content. In the fourth chapter, the results were presented and analyzed, and the fifth chapter included a presentation of the conclusions, recommendations, and proposals, and then the sources.